2019
DOI: 10.1186/s41239-019-0147-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating self-directed learning and technology readiness in blending learning environment

Abstract: Blended Learning (BL) creates a 'rich' educational environment with multiple technologyenabled communication forms in both face-to-face and online teaching. Students' characteristics are closely related to the learning effectiveness in the BL environment. Students' ability to direct themselves in learning and to utilise learning technologies can affect student learning effectiveness. This study examined the impacts of self-directed learning, technology readiness, and learning motivation on the three presences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
1
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(251 citation statements)
references
References 66 publications
6
179
1
9
Order By: Relevance
“…This is because one of the members of the group has ever joined scientific groups in the school so that they got used to doing with the investigation activity and problem-solving. This investigation activity is able to make the students become independent learner and encourages them to be responsible to their own learning, learning effectiveness, and critical thinking (Smallhorn et al, 2015;Kopzhassarova et al, 2016;Geng et al, 2019).…”
Section: The Implementation Of the Science Contextbased Inquiry Learnmentioning
confidence: 99%
“…This is because one of the members of the group has ever joined scientific groups in the school so that they got used to doing with the investigation activity and problem-solving. This investigation activity is able to make the students become independent learner and encourages them to be responsible to their own learning, learning effectiveness, and critical thinking (Smallhorn et al, 2015;Kopzhassarova et al, 2016;Geng et al, 2019).…”
Section: The Implementation Of the Science Contextbased Inquiry Learnmentioning
confidence: 99%
“…This was acknowledged by Gehlen-Baum and Weinberger (2012) who stated that students use their mobile devices for annotating lecture slides, taking notes, looking at lecture-related websites and looking at lecture-related documents. Guided intervention in mobile learning is a concern to be taken into consideration when we talk about blended learning as Geng et al (2019) implied that teaching presence is critical to the course and facilitation. Teaching presence can be defined as the design, facilitation, and direction of cognitive and social processes for the purpose of realizing personally meaningful and worthwhile educational learning outcomes (Anderson et al 2001).…”
Section: Guided Mobile Learning and Academic Performancementioning
confidence: 99%
“…The absence of suitable devices or their incompatibilities may hinder the effectiveness of the learning experience designed by the instructors. According to [22], many studies assessed students' readiness to use technology by examining several factors such as personal innovation, perceived usefulness, performance expectancy, effort expectancy, social influence, perceived playfulness, self-management of learning, using the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and User of Technology (UTAUT) [23] [24]. In the same article, [22] referred to [25] who concluded that most students in higher learning institutions nowadays are what we commonly call digital natives.…”
Section: Resultsmentioning
confidence: 99%